Maturing as Believers Through Interreligious Encounters - Soetomo, Greg, SJ (Archīum Ateneo, 2020)
We believe that God is present, actively at work, and reveals Himself in various ways through the religions of humankind. Interreligious dialogue in all its forms can be mutually enriching and can help us in knowing and loving God more and in maturing as believers. It can also promote harmony and facilitate collaboration in building up the human family. The effective pastoral worker is one who is open to God’s Spirit in engaging with people of other faiths, and one who promotes meaningful inter-religious dialogue among peoples on all levels.